Geological features and genesis of the Dyusembay Central (Sayakhat) ore deposit - Galym Zh. Nurzhanov; Vladimir V. Kuznetsov; Pavel A. Nicenko; Nelly G. Kudryavtseva; Tatiana P. Kuznetsova; Mergen M. Murzagulov (Руды и металлы)
The article considers the geological features and ore composition of the Dyusembay Central (Sayakhat) lead-zinc deposit in the Karsakpai metallogenic complex in the Central Kazakhstan. Historically, the complex was considered industrially significant in terms of iron ores, rather than of lead, zinc, and copper. It is shown that the ore deposit is composed of tuffaceous, silty-sandstone, carbonaceous-terrigenous (ore-hosting), terrigenous, and volcanogenic rocks assigned to the lower subformation of the Zhilandysai Formation of the Upper Proterozoic. The subvolcanic rocks identified and outlined in the area of the ore deposit belong to vent volcanic facies and are represented by felsic automagmatic breccias. All the rock complexes developed within the deposit have undergone multiple alterations: the regional, postvolcanic, contact, and hydrothermal (near-ore) ones. Commercial ores are represented by veinlet-disseminated sulfide mineralization in carbonaceous mudstones and silty sandstones, regionally and metasomatically altered to varying degrees. The ore bodies are composed of heterogeneous mi- neral assemblages corresponding to various stages and phases of the ore formation. The composition and structural and textural features of the ores reflect the long and complicated history of their formation. It is concluded that this ore deposit belongs to a new formational type of veinlet-disseminated stratified lead-zinc deposits localized in black shale sequences, with a significant role of volcanic activity and regional metamorphism, and is a remobilized SEDEX-type ore deposit.